‘Bulun in Winter Is So Sad’: A. Bogolepov about Everyday Life in Polar Yakutia, 1913–1916 - Lilia I. Vinokurova; Alexander A. Suleymanov; Svyatoslav I. Fedorov (Oriental Studies)
Goals. The article introduces an unknown manuscript by A. Bogolepov titled ‘Bulun Village of Verkhoyansk District (Yakutsk Oblast)’ and compiled during an exile to the isolated Arctic locality of Yakutia. The narrative was written before the revolutionary events of 1917 and is of certain interest since it lacks any political bias, being characterized by restrained neutrality and sufficient depth of observations over everyday realias of the small northern settlement. A. Bogolepov’s text is attractive for the breadth of issues covered, its consonance with the social and cultural problems faced by the era and discussed by the advanced public. So, it seems reasonable enough to publish the identified document for further discussion in an interdisciplinary perspective. Materials and methods. The manuscript was discovered at the State Archive of Irkutsk Oblast (Coll. 293 ‘East Siberian Department of the Russian Geographical Society’). Furthermore, in search of additional data on the former’s author we investigated the State Archive of Altai Krai (Barnaul), State Archive of Krasnoyarsk Krai (Krasnoyarsk), National Archive of Sakha-Yakutia (Yakutsk), Archive of the Russian Academy of Sciences (Moscow) and its St. Petersburg Branch, and the efforts have yielded a variety of precious finds. The methodological basis rests on the principles characteristic of the field the researchers are actually engaged in — cryoanthropology. Results. The discovered materials open a previously unknown page in the Yakut pre-Soviet Northern studies. A. Bogolepov’s manuscript is rich in data on natural conditions, economic and cultural activities in the small remote settlement somewhat representing the polar world in miniature. The author highlights the interpenetration of Russian and Yakut cultures, mentions some specific local sociocultural phenomena resulting from the geographical location and climatic features. The long cold period — as is stressed by A. Bogolepov — shapes the entire life cycle of the settlement: it completely determines the functioning of the transport network, household and trade agendas, everyday life and leisure pursuits of locals. The isolation and scarcity of social activity, temporal and event-based ‘frozen’ everyday life of the northern society are emphasized. The manuscript is an important source for the research of cryoanthropology, and also contains valuable information on Yakutia’s socioeconomic and cultural history throughout the early decades of the twentieth century.